2020
DOI: 10.3390/plants9070829
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Relating to Flowering Time, Flag Leaf and Awn Characteristics in a Novel Triticum dicoccum Mapping Population

Abstract: Tetraploid landraces of wheat harbour genetic diversity that could be introgressed into modern bread wheat with the aid of marker-assisted selection to address the genetic diversity bottleneck in the breeding genepool. A novel bi-parental Triticum turgidum ssp. dicoccum Schrank mapping population was created from a cross between two landrace accessions differing for multiple physiological traits. The population was phenotyped for traits hypothesised to be proxies for characteristics associated with imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…This QTL was found to be a cis-element GATA box in Vrn-A3 (located on chromosome 7AS), which suppressed the late-flowering (photoperiod sensitive) Ppd-A1b allele (Nishimura et al 2018 ). A QTL controlling flowering time was also reported on 7B linked to Vrn-B3 in an emmer mapping population (Wright et al 2020 ). Takenaka and Kawahara ( 2012 ) identified novel loss of function alleles in tetraploid Ppd-A1 in emmer wheat that do not confer PI but may induce small variations in flowering time.…”
Section: Progenitor Species Provide Additional Variation For Flowerin...mentioning
confidence: 83%
See 2 more Smart Citations
“…This QTL was found to be a cis-element GATA box in Vrn-A3 (located on chromosome 7AS), which suppressed the late-flowering (photoperiod sensitive) Ppd-A1b allele (Nishimura et al 2018 ). A QTL controlling flowering time was also reported on 7B linked to Vrn-B3 in an emmer mapping population (Wright et al 2020 ). Takenaka and Kawahara ( 2012 ) identified novel loss of function alleles in tetraploid Ppd-A1 in emmer wheat that do not confer PI but may induce small variations in flowering time.…”
Section: Progenitor Species Provide Additional Variation For Flowerin...mentioning
confidence: 83%
“…Diversity in flowering time has been further characterised by several studies in tetraploids wheats (Nishimura et al 2018 ; Wright et al 2020 ; Würschum et al 2019 ). Alleles of the Ppd-A1 associated with early flowering (but distinct from the Ppd-A1a alleles described by Wilhelm et al 2009 ) were detected in emmer wheat by Nishimura et al ( 2018 ) who also identified an early heading date QTL associated with Vrn-A3 .…”
Section: Progenitor Species Provide Additional Variation For Flowerin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Wright et al. (2020) created a novel biparental population using two tetraploid landrace accessions differing for multiple physiological traits and identified one QTL for FLW on chromosome 5B based on a 35K wheat SNP array.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Aegilops speltoids, a close relative of hexaploid wheat (bread wheat), contains 6 heat stress transcription factors (HSFC1b, HSFB2a, HSFB2b, HSFA3, HSFA5 and HSFA9; Seni et al, 2021), which can be used in breeding programmes of wheat for HT tolerance at reproductive stage (Jakhu et al, 2021). Likewise, in emmer wheat, the alleles (Ppd-A1) are associated with early flowering (Nishimura et al, 2018), while the QTL that suppressed the late flowering in emmer wheat was detected on 7B chromosome and is linked to the Vrn-B3 gene (Wright et al, 2020), which will be helpful in protecting plant from male sterility during HT stress. Similarly, in rice, Cao et al (2022) found a QTL (qHTH5) in Oryza rufipogon at chromosome 5 and transfered it to Oryza sativa, which increased the tolerance in O. sativa at the heading stage, while its suppression increased its susceptibility to HT stress.…”
Section: Utilization Of Wild Species In Breeding Programmes To Enhanc...mentioning
confidence: 99%